Value : the four cornerstones of corporate finance - Koller, Tim.; Dobbs, Richard; Huyett, Bill.; McKinsey and Company (Hoboken, N.J. : John Wiley & Sons, 2011)
"An accessible guide to the essential issues of corporate finance While you can find numerous books focused on the topic of corporate finance, few offer the type of information managers need to help them make important decisions day in and day out. Value explores the core of corporate finance without getting bogged down in numbers and is intended to give managers an accessible guide to both the foundations and applications of corporate finance. Filled with in-depth insights from experts at McKinsey & Company, this reliable resource takes a much more qualitative approach to what the authors consider a lost art. Discusses the four foundational principles of corporate finance. Effectively applies the theory of value creation to our economy. Examines ways to maintain and grow value through mergers, acquisitions, and portfolio management. Addresses how to ensure your company has the right governance, performance measurement, and internal discussions to encourage value-creating decisions. A perfect companion to the Fifth Edition of Valuation, this book will put the various issues associated with corporate finance in perspective"--Provided by publisher.
Includes index.
oif 15/09/14
Loan
Keywords: Corporations -- Valuation; Corporations -- Finance; Stockholder wealth